Does Diversity Climate Matter? The More Respected I Feel, the Better I Can Do: Unravelling the Mechanisms Enabling Employees’ Extra-Role Performance - Belachew Kassahun Ayele; Wenbing Wu; Chong Chen (Behavioral Sciences)
The current study examined how a diversity climate promotes employees’ extra-role performance and how the roles of workplace belongingness and thriving at work mediate this effect. Furthermore, this study investigated the sequential mediation effect of workplace belongingness and thriving at work in the aforesaid relationship. This study also tested the leaders’ positive affective presence as a moderator in the effect of diversity climate on extra-role performance. This study incorporated the self-determination theory to forge theoretical connections. As a result, a three-wave survey consisting of 349 employees revealed support that a diversity climate has a positive impact on employees’ extra-role performance, both directly and indirectly, through workplace belongingness and thriving at work. Meanwhile, leaders’ positive affective presence strengthens the diversity climate’s influence on workplace belongingness. Our findings supported all proposed hypotheses. Finally, this study discusses the theoretical and practical contributions of the results.